The integrated approach involving the AHP and TOPSIS methods in assessing financial condition of the companies of the telecommunications sector - Jędrzejczak-Gas, Janina (Research Papers of Wrocław University of Economics, 2018)
The aim of the paper is to make a synthetic evaluation of the financial condition of telecommunications sector companies listed on the NewConnect market in the years 2012-2015. Integrated approach, which includes the use of the AHP and TOPSIS methods, is presented and applied. The paper is both theoretical and empirical: the first part describes the process of developing a synthetic measure and the second contains the analysis and assessment, on the basis of the presented synthetic measure. Next, the studied companies are ranked and grouped by assigning the companies to four typological groups. The conducted calculations show that, the analysed companies had a varying financial condition. Most often it could be described as average and good. A positive sign is that, in the analysed time period, financial condition improved in 70% of the studied companies
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 519, s. 109-121
Keywords: financial condition; telecommunications sector; AHP method; TOPSIS method; synthetic measure; kondycja finansowa; przedsiębiorstwa sektora telekomunikacyjnego; metoda AHP; metoda TOPSIS; miernik syntetyczny